Differences And Different Responses In Inflammation And Pneumonia (A Mini Review) - Yulia Putri; Dina Keumala Sari; Yunita Sari Pane; Ririe Fachrina Malisie; Nuraiza Meutia; M. Ichwan (International Journal of Ecophysiology, 2024)
A major public health issue with high morbidity and short and long term mortality in all age groups worldwide, pneumonia is a typical acute respiratory infection that affects the alveoli and distal airways. Community-acquired pneumonia and hospital-acquired pneumonia are the two main categories of pneumonia. Pneumonia can be brought on by a wide range of microbes, including bacteria, respiratory viruses, and fungus. The incidence of these microbes varies greatly geographically. Pneumonia affects susceptible people more frequently, such as young children under the age of five and older persons with a history of chronic illnesses. Pathogen features play a less important influence in disease development than does the host immune response. Patients with pneumonia frequently exhibit respiratory and systemic symptoms, and radiological findings as well as clinical presentation are used to make the diagnosis. It is essential to identify the microorganisms that are causing the disease because delayed or ineffective antimicrobial therapy can have negative effects. The treatment of pneumonia will be enhanced by new antibiotic and non-antibiotic medicines, as well as quick and precise diagnostic tools that can identify bacteria and drug resistance.